Crisis Management in Managing Hotels in Labuan Bajo During The Covid-19 Pandemic - Reynaldo Angga Siagian; Gregorius A. Berybe; Thyophoida W.S. Panjaitan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Covid-19 pandemic at the beginning of 2020 had a significant impact on all types of businesses which resulted in a crisis in all types of businesses in Labuan Bajo, one of which was the hotel industry in Labuan Bajo. The Covid-19 pandemic resulted in the room occupancy rate experiencing a drastic decline, one of which was due to the lack of domestic and foreign tourist visits. This situation requires the hotel industry to revise, innovate, and change its business strategy. This study aims to explore crisis and disaster management for tourism, especially in the hospitality industry by considering a strategic approach from the hotel management perspective. The government and local stakeholders in an effort to grow the hotel industry in Labuan Bajo. One of the strategies carried out by the government in an effort to grow the room occupancy rate is by establishing certification in the hotel industry that establishes health protocols based on Cleanliness (Cleanliness), Health (Health), Safety (Security), and Environment Sustainability (Environmental Sustainability) or CHSE. If it is known that each hotel has implemented and made improvements in terms of service to consumers based on the CHSE, the government will provide subsidies or funds intended for the purchase of tools related to handling COVID 19 in the hotel area. In addition, giving a CHSE Certificate to a hotel will create a feeling of security for consumers to stay at the hotel. The hotel also needs to identify what consumers need and want, as well as consumer behavior patterns, especially during the Covid 19 pandemic which pays attention to cleanliness, health, and sustainability, so hotel management in offering and carrying out hotel operational activities pays attention to the healthy lifestyle of consumers.